2023
DOI: 10.3390/catal13020387
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Catalysts with MIRA21 Model in Heterogeneous Catalytic Hydrogenation of 2,4-Dinitrotoluene

Abstract: Although 2,4-dinitrotoluene (DNT) hydrogenation to 2,4-toluenediamine (TDA) has become less significant in basic and applied research, its industrial importance in polyurethane production is indisputable. The aim of this work is to characterize, rank, and compare the catalysts of 2,4-dinitrotoluene catalytic hydrogenation to 2,4-toluenediamine by applying the Miskolc Ranking 21 (MIRA21) model. This ranking model enables the characterization and comparison of catalysts with a mathematical model that is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The palladium content of the fresh catalyst was 1.61 wt%, which did not show a significant decrease after multiple cycles (1.60 wt%). Based on the results of the reuse tests and ICP measurements, it can be stated that the developed catalyst is stable, owing to the strong interaction between the noble metal and its support 11 14 , 21 , 36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The palladium content of the fresh catalyst was 1.61 wt%, which did not show a significant decrease after multiple cycles (1.60 wt%). Based on the results of the reuse tests and ICP measurements, it can be stated that the developed catalyst is stable, owing to the strong interaction between the noble metal and its support 11 14 , 21 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The developed Pd/CoFe 2 O 4 bentonite-based catalyst was compared to 14 other systems 11 , 12 , 12 , 13 , 36 applied in DNT hydrogenation by using the MIRA21 model 14 . It was found that the bentonite-based catalyst has a MIRA21 number of 11.09, which is just slightly lower than the best (11.50) and ranks as 8th within the list of 15 catalysts (see Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIRA21 (MIskolc RAnking 21) model has been established for the characterization, comparison, and ranking of catalysts with a mathematical model that is based on a descriptor system [19]. In our previous work, hydrogenation reactions of nitrobenzene and 2,4-dinitrotoluene were examined based on four groups of parameters such as catalyst performance, reaction conditions, catalyst conditions, and sustainability parameters [20]. The setting of the parameter set was compiled based on the information available in various scientific publications.…”
Section: Introductionmentioning
confidence: 99%
“…Exploratory data analysis of the literature data of 2,4-dinitrotoluene hydrogenation catalysts was carried out. Based on the MIRA21 model, data was extracted from scientific articles and converted into a catalyst library [20]. Descriptive and statistical analysis provides an opportunity to study the MIRA21 model descriptor system and the correlations between catalyst physicochemical properties and catalyst performance parameters such as conversion and selectivity.…”
Section: Introductionmentioning
confidence: 99%